Community-based monitoring, assessment and management of data-limited inland fish stocks in North Rupununi, Guyana - Shephard, S.; Edwards, K.; George, S.; Joseph, E.; James, S.; David, O.; Persaud, A.; Watson, C.; Vliet, N. van (Wiley, 2023)
Inland fisheries are important for food security in communities around the world, especially in developing countries. In North Rupununi, Guyana, the state of exploited stocks is poorly understood, and fishery monitoring and assessment are challenging because diverse fishing gears and target species are distributed across a heterogeneous landscape. This complexity created an opportunity for community-based monitoring (CBM) to support data-limited assessment. Standardised CBM was established for the North Rupununi as part of a new inland fisheries management plan initiated by indigenous community groups with support from the government. Quantitative length-based assessments undertaken for target stocks suggested moderate levels of exploitation consistent with local perception. Our study highlights that local experts and community participants with different levels of training can collect accurate biodiversity data. Further development of CBM is important in North Rupununi. We recommend using local ecological knowledge indicators to track spatial and temporal patterns in exploitation and fish stock status.